Code of Silence (The Dance Current, 2017)
Fifteen years ago, Lisa, a dance conservatory student, became pregnant. She was told in no uncertain terms by her school’s directors that abortion was recommended, and that she wouldn’t be allowed to continue attending the conservatory otherwise. It was made clear to her that the fact that her pregnancy would be in its seventh month at the time of graduation...

«Sous la ceinture»: La culture du viol, «pas une lubie de féministe» - Chabot, Kim (HuffPost, 2016)
«Sous la ceinture»: La culture du viol, «pas une lubie de féministe»
Keywords: Bibliographie; Nettoyer

Winnipeg comedy club bans discrimination, hatefulness, harassment | CBC News - Gibson, Shane (CBC, 2018)
Wee Johnny’s comedy room posted a sign this week warning that anyone violating a new anti-harassment policy — which bans “sexism, racism, homophobia, transphobia, physical intimidation or any other form of abusive behaviour” — may be asked to leave the club.

#ThisIsArtSchool Is Exposing Allegations Of Racism & Sexual Abuse In Montreal Universities - Elliot, Teddy (MTL Blog, 2020)
As stories of racism and discrimination towards Black, Indigenous, and people of colour continue to dominate public discourse, more and more shocking allegations come to light about the lived experiences of systemic racism.
Keywords: Bibliographie; Nettoyer